From Active Participant to Active Researcher: What Do Young People Understand about Research? - Amelia Alias; Nurfaradilla Mohamad Nasri; Mohd Mahzan Awang (MDPI AG, 2023)
This paper discusses the outcomes of an initiative to empower young people as active researchers. It highlights participants' understandings of their role as researchers in terms of the meaning of research, the research processes, and the participants' competences, knowledge, and skills. It describes a process that a group of 15 child councillors aged between 15 and 17 years went through that was aimed at equipping them with the knowledge and skills to conduct their research. Based on the data presented, it was clear that from the participants' point of view, the research process was challenging and time-consuming since it entailed several steps that needed to be carried out with careful attention to detail. Despite this, the participants were confident in their ability to undertake independent research, albeit with guidance from adults. Their research abilities and knowledge of child rights improved because of their having conducted research. The participants also noted that their learning was more meaningful when they were engaged in the subject topic, supporting the notion that learning by doing is vital. Due to its emphasis on acquiring children's meaningful participation and illustrating the complex reality of being a part of research, this study has made important contributions to the small body of literature on child participation in Malaysia.